Positive Parenting sebagai Faktor Protektif terhadap Resiliensi Anak Usia Dini - Dian Widiantari (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2026)
This research is motivated by the still high vulnerability of early childhood in facing environmental pressures that have an impact on low resilience, so it is necessary to strengthen protective factors in the family through positive parenting. This study aims to analyze the level of positive parenting, relationships, and the influence of positive parenting as protective factors for early childhood resilience. The approach used is quantitative using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The research sample amounted to 1,092 respondents who were selected through purposive sampling techniques. The research instrument was tested using external model and inner model analysis. The results showed that all indicators of positive parenting and early childhood resilience variables met the validity and reliability criteria. The path coefficient value of 0.781 showed a positive and strong relationship. The results of the hypothesis test showed a significant influence with a T-statistic of 35.67 (>1.96) and a P-value of 0.000 (<0.05). An R² value of 0.61 indicates that positive parenting is able to explain 61% of the variation in early childhood resilience. This study concludes that positive parenting as a protective factor has a positive, strong, and significant effect on early childhood resilience. These findings confirm the importance of positive parenting in the family and its relevance to the values of Islamic education based on rahmah, amanah, and uswah hasanah.